IMPROVE PROBLEM SOLVING ABILITY STUDENTS IN STORY THROUGH USE OF MEDIA CARDS AND POSTER TO IV A SD INPRES PERUMNAS I MAKASSAR - Sulsiani, . (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2015)
This type of research is a classroom action which aims to improve students' skills in solving word problems through the use of media cards and posters for the classroom IV.A SD Inpres Perumnas I Makassar. The research was conducted at SD Inpres Perumnas I Makassar. The study population was IV.A graders semester of academic year 2012/2013. This data was obtained through observation, and achievement test each end of the cycle. Data analysis is a quantitative and qualitative analysis. The purpose of this study is: (i) to assess the implementation process of learning with the use of media cards and posters in solving word problems in class SD Inpres Perumnas I Makassar; (ii) to improve the ability to solve word problems through the use of media cards and posters in elementary grade students SD Inpres Perumnas I Makassar. The results showed that (i) the use of media cards and posters in solving word problems can improve student learning outcomes, (ii) Students' motivation in solving word problems has increased. This is evident from the achievement of the indicators of success in solving word problems. The improvement can be seen from the average value of an evaluation test on the first cycle of 61.14 and the second cycle increased to 75